2011
DOI: 10.1891/0886-6708.26.2.218
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Poor Parenting on Male and Female Dating Violence Perpetration and Victimization

Abstract: This study examines the effects of poor parenting on dating violence perpetration and victimization among approximately 900 males and females from the National Longitudinal Survey of Adolescent Health (Add Health). Results revealed that more physical abuse and low parental warmth were linked to greater substance use and higher rates of delinquency. In addition, low parental warmth, more neglect, and greater delinquency had positive direct effects on dating violence perpetration, whereas more physical abuse, lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 39 publications
3
33
1
Order By: Relevance
“…Other studies of IPV have developed the idea of direct transmission of violent behaviors, either as the child witnesses parental violence or garners direct experience as a victim of the parent’s use of harsh discipline (Jouriles et al, 2012; Kinsfogel & Grych, 2004; Tyler, Brownridge, & Melander, 2011). In a recent review and assessment of this literature tradition, Foshee and colleagues (2011) concluded that child abuse, relative to witnessing marital violence, has a greater influence on IPV.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies of IPV have developed the idea of direct transmission of violent behaviors, either as the child witnesses parental violence or garners direct experience as a victim of the parent’s use of harsh discipline (Jouriles et al, 2012; Kinsfogel & Grych, 2004; Tyler, Brownridge, & Melander, 2011). In a recent review and assessment of this literature tradition, Foshee and colleagues (2011) concluded that child abuse, relative to witnessing marital violence, has a greater influence on IPV.…”
Section: Introductionmentioning
confidence: 99%
“…Studies focused specifically on TDV have shown that positive parenting practices, such as warmth, support, and responsiveness, reduce the likelihood of adolescents’ involvement in TDV (Brendgen, Vitaro, Tremblay, & Lavoie, 2001), while low levels of positive parenting practices increase the risk of TDV perpetration and victimization (Tyler, Brownridge, & Melander, 2011). What is not clear, however, is whether positive parenting practices moderate the link between IPV exposure and TDV.…”
mentioning
confidence: 99%
“…Adolescents exposed to family aggression may adopt normative beliefs that are accepting of dating violence, 34,63 have dysfunctional family relationships that lead to increased dependence on partners, and develop low self-worth, each of which could increase adolescent risk for becoming involved in and remaining in abusive relationships. Decreasing family aggression should be a goal of family-based programs for preventing DVV.…”
Section: Discussionmentioning
confidence: 99%